"Water-in-salt" polymer electrolyte for Li-ion batteries. Issue 9 (12th August 2020) - Zhang, Jiaxun; Cui, Chunyu; Wang, Peng-Fei; Li, Qin; Chen, Long; Han, Fudong; Jin, Ting; Liu, Sufu; Choudhary, Hema; Raghavan, Srinivasa R.; Eidson, Nico; von Cresce, Arthur; et al.
Abstract : An extended electrochemical stability window of 3.86 V is achieved at 12 mol kg −1 aqueous polymer electrolyte enabled 3 V full cells with an unprecedented high initial CE of 90.50% and average CE of 99.97%. Abstract : Recent success in extending the electrochemical stability window of aqueous electrolytes to 3.0 V by using 21 mol kg -1 "water-in-salt" (WiS) has raised a high expectation for developing safe aqueous Li-ion batteries. However, the most compatible Li4 Ti5 O12 anodes still cannot use WiS electrolyte due to the cathodic limit (1.9 V vs. Li/Li + ). Herein, a UV-curable hydrophilic polymer is introduced to further extend the cathodic limit of WiS electrolytes and replace the separator. In addition, a localized strongly basic solid polymer electrolyte (SPE) layer is coated on the anode to promote the formation of an LiF-rich SEI. The synthetic impacts of UV-crosslinking and local alkaline SPE on the anodes extend the electrochemical stability window of the solid-state aqueous polymer electrolyte to ∼3.86 V even at a reduced salt concentration of 12 mol kg −1 . It enables a separator-free LiMn2 O4 //Li4 Ti5 O12 aqueous full cell with a practical capacity ratio (P/N = 1.14) of the cathode and anode to deliver a steady energy density of 151 W h kg −1 at 0.5C with an initial Coulombic efficiency of 90.50% and cycled for over 600 cycles with an average Coulombic efficiency of 99.97%, which has never been reported before for an aqueous LiMn2 O4 //Li4 Ti5 O12 full cell. This flexible and long-duration aqueous Li-ion battery with hydrogel WiSE can be widely used as a power source in wearable devices and electrical transportations where both energy density and battery safety are of high priority. An ultra-thick LTO electrode with UV-curable polymer electrolyte as the binder is demonstrated as a solid state battery electrode. And a high-voltage (7.4 V) solid-state bipolar cell is assembled with a solid-state UV-curable polymer as the electrolyte.